Patterns in Opioid Prescription for Patients Operatively Treated for Ankle Fractures Following Implementation of 2017 Ohio Opioid Prescriber Law. Issue 4 (16th October 2019) - Glogovac, Georgina; Fitts, Jamal; Henning, Jordan; Dixon, Tonya; Laughlin, Richard T.
Category: Ankle, Trauma Introduction/Purpose: The use of prescription opioids has risen sharply over the last few decades as pain management has become increasingly recognized as an essential aspect of patient care. In August 2017, Ohio implemented a law limiting the quantity of opioid medications a provider could prescribe for the treatment of acute pain. Specifically, a prescriber may not prescribe more than 7 days of opioids in the first prescription for an acute pain episode and the total morphine equivalent dose (MED) cannot exceed an average of 30 MEDs a day. The purpose of this study is to report patterns of opioid prescription for patients treated operatively for ankle fractures after implementation of the 2017 Ohio Opioid Prescriber Law in comparison to the previous year. Methods: A total of 152 patients operatively treated for isolated ankle fractures during two six-month periods, January 2017 to July 2017 (n=73) and January 2018 to July 2018 (n=79), were retrospectively identified using CPT codes. The earlier time period includes patients treated before implementation of the Ohio Opioid Prescriber Law, and the later time period represents patients treated after implementation of the law. Preoperative and postoperative patient narcotic use was reviewed using a legal prescriber database. The prescription search was limited to prescriptions prescribed within one year prior to surgery and 6 months postoperatively. Total number of prescriptions, quantity of pills, and milligrams of morphine per patient prescribed during the 90- day postoperative period were compared between those treated before and those treated after implementation of the law. Average number of pills and average milligrams per morphine per prescription were also compared. Statistical analysis was conducted using t-tests and fisher exact tests. Results: The average number of opioid prescriptions prescribed per patient in the 90-day postoperative period was 2.3 in the pre-law group and 1.95 in the post-law group (p=0.35). The average milligrams of morphine prescribed per patient dropped from 942.41 mg pre-law to 645.25 mg post-law (p=0.18). Differences in the average number of pills per prescription pre- and post-law (49.72 vs. 36.06) and average milligrams of morphine per prescription (383.11 mg vs. 277.56 mg) were statistically significant (p=0.002 and p=0.014, respectively). Differences in age, gender, Charlson Comorbidity Index, BMI, preoperative narcotic use, and postoperative narcotic use exceeding 90 days were not statistically significant between groups (p>0.05). Conclusion: Following the implementation of the 2017 Ohio Opioid Prescriber Law, there was a significant decline in the number of pills per prescription and milligrams of morphine per prescription in patients operatively treated for isolated ankle fractures. The presence of a downward trend in the quantity of opioids prescribed in this patient cohort suggests the effectiveness of the state prescriber law and is promising in the setting of the current opioid epidemic in the United States.